Relationship Between Career Interest and Career Decision-Making of Grade 12 Learners in Township Secondary Schools in South Africa - Oluwakemi B Ajayi; Moeniera Moosa; Peter JO Aloka (Athens Institute for Education and Research, 2023)
This study examined the relationship between career interests and career decision-making of grade 12 learners in township secondary schools in South Africa. The correlational survey research design was adopted. The sample size comprised 204 grade 12 learners selected from six township secondary schools. The career interest and career decision-making scales were used to collect data from the learners. The inferential statistics such as Pearson correlation, Analysis of Variance (ANOVA), and regression analysis were used to analyse data. The results indicated that the correlation between enterprising career interest and career decision-making was established to be the strongest (r=0.535, n=204, p<0.001), followed by the relationship between adventurous career interest and career decision-making (r=0.465, n=204, p<0.001), but operational career interest had the least relationship with career decision-making, r (204)=0.284, p<0.001. The study concludes that the career interest model, F (9, 194)=17.403, p<0.01, is a significant predictor of career decision-making among the 12th grade learners. The study recommends that school psychologists should do early assessment of learners to ascertain their career interests.